Australian Dance Theatre Adelaide season April 2nd-11th Opera Theatre. - Jahnsons, Silvia ([Australia] : Australian Dance Theatre, 1981)
Shows an illustration of two male dancers, one lying down and supporting the foot of the other who is moving above him. Red and black with white lettering.
Catalogue record generated as part of a batch load.
Australian Dance Theatre
Also available online
Keywords: Australian Dance Theatre -- Posters; Dance companies -- Australia -- Posters; Modern dance -- Australia -- Posters